Properties of high-workability concrete with recycled concrete aggregate - Safiuddin (2011)
This study presents the effects of recycled concrete aggregate (RCA) on the key fresh and hardened properties of concrete. RCA was used to produce high-workability concrete substituting 0-100% natural coarse aggregate (NCA) by weight. The slump and slump flow of fresh concretes were determined to ensure high workability. In addition, the compressive, flexural and splitting tensile strengths, modulus of elasticity, and permeable voids of hardened concretes were determined. The test results revealed that RCA significantly decreased the workability of concrete. RCA also affected the compressive strength, modulus of elasticity, and permeable voids of concrete. At the age of 28 days, the concrete with 100% RCA provided 12.2% lower compressive strength and 17.7% lesser modulus of elasticity than the control concrete. Also, 100% RCA increased the permeable voids of 28-day old concrete by 8.2%. However, no significant negative impact of RCA was observed on the flexural and splitting tensile strengths of concrete.